Wine adulteration and its detection based on the rate and the concentration of free amino acids - Csapó, János; Albert, Csilla (Acta Agraria Debreceniensis, 2018)
Following the definition of wine adulteration, the authors briefly review its history from ancient times to present day and describe the methods that are applied for adulteration of wine from the historical point of view. More space is devoted to the Hungarian wine adulteration and to the detailed reports of the early methods, which attempted to discover fake wine. It describes in detail the current situation of wine adulteration and the fight against counterfeiting. The second half of the review article presents some examples of the analytical chemistry techniques with which fake wines can be detected. In doing so, priority is given to the discussion of high performance liquid chromatography and gas chromatography applications. The end of this paper describes the free amino acid content of wines, and the possibilities of using the results for detection of wine adulteration.